Long-term effects of altitude on changes in intestinal flora in a young and middle-aged population: a longitudinal analysis before and after 6 months of entry to high altitude - Kan, Hongjiao; Yuan, Yingna; Zhao, Kaijie; Sun, Xiuting; Li, Junlian; Huo, Farong; Zhang, Xiaoyan (Frontiers in Microbiology, 2026)
IntroductionThe low oxygen environment of high altitude predisposes to imbalances in gut flora and changes in metabolites that can affect metabolic health. The relationship between gut flora and the health of sedentary populations at high altitude has been extensively studied. However, the dynamic changes of gut flora and its metabolomics after entering high altitude and the long-term effects on the health of young and middle-aged people have not been studied enough. This study aims to investigate the patterns of gut microbiota and metabolomics changes in middle-aged and young adults during the week preceding ascent to 4,500 m above sea level and within the 6 months following high-altitude exposure.MethodsA total of 70 healthy young and middle-aged people were collected from November 2023 to June 2024 from an altitude of about 1,600 to 4,500 m, and their stool samples were collected. 16S rRNA sequencing and liquid-liquid-mass spectrometry (LC-MS/MS) were used to detect the changes in the composition of the gut microorganisms and the differential metabolites of the intestinal tract in the young and middle-aged people before and after they entered the altitude, and the changes in the abundance and composition of the gut flora and their metabolomics were analyzed. Abundance and composition and the changes in their metabolomics.ResultsThe results showed that the largest differences in the abundance of intestinal microorganisms at the phylum and genus levels were Firmicutes and Blautia in High-altitude group (HG) compared with Low-altitude group (PG), and the alpha diversity (α-diversity) and abundance of intestinal microorganisms in HG were lower than those in PG. The differences in the flora at the phylum level were significantly higher in the Actinobacteriota (Actinobacteria) relative abundance of HG compared with that of PG, and the relative abundance of PG was higher in the Actinobacteria (Actinobacteria) phylum than that of PG. Actinobacteriota (phylum) relative abundance was significantly higher in HG compared to PG (p < 0.001). At the genus level, the relative abundance of Blautia, Bifidobacterium, Fusicatenibacter, and Anaerestipes was significantly higher in HG compared to PG (p < 0.05 or p < 0.001). The compound classes with the largest ratio of HG to PG were Lipids and lipid-like molecules (25.15%), Lipids and lipid-like molecules (25.15%), and Lipids and lipid-like molecules (25.15%). There was a correlation between differential metabolites in HG and PG samples. Volcano plots showed 456 up-regulated and 425 down-regulated metabolites were identified for HG compared to PG. Six major classes of metabolic pathways were detected for KEGG.DiscussionIn conclusion, significant changes in the diversity, abundance, composition and differential metabolites of the intestinal gut flora occurred before and after entering high altitude in young and middle-aged populations, which may be important for the adaptation of young and middle-aged populations in the plateau environment.